2021
DOI: 10.3390/ijms22136812
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Water-Soluble C60 Fullerene Nanoparticles on the Ischemia-Reperfusion Injury of the Muscle Soleus in Rats

Abstract: The biomechanical parameters of muscle soleus contraction in rats and their blood biochemical indicators after the intramuscular administration of water-soluble C60 fullerene at doses of 0.5, 1, and 2 mg/kg 1 h before the onset of muscle ischemia were investigated. In particular, changes in the contraction force of the ischemic muscle soleus, the integrated power of the muscle, the time to achieve the maximum force response, the dynamics of fatigue processes, and the parameters of the transition from dentate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
16
0
4
Order By: Relevance
“…C 60 fullerenes can efficiently capture free radicals with their abundant conjugated double bonds and low-energy LUMO orbitals. Ritter and coworkers investigated intramuscularly administered C 60 fullerene aqueous solution for therapeutic and preventive value as an antioxidant [ 173 ]. The study found that C 60 fullerene aqueous solution at a dose of 1 mg/kg reduces severity of ischemic damage in rat muscle soleus by 60–75%.…”
Section: Biomedical Fullerene Nanoparticlesmentioning
confidence: 99%
“…C 60 fullerenes can efficiently capture free radicals with their abundant conjugated double bonds and low-energy LUMO orbitals. Ritter and coworkers investigated intramuscularly administered C 60 fullerene aqueous solution for therapeutic and preventive value as an antioxidant [ 173 ]. The study found that C 60 fullerene aqueous solution at a dose of 1 mg/kg reduces severity of ischemic damage in rat muscle soleus by 60–75%.…”
Section: Biomedical Fullerene Nanoparticlesmentioning
confidence: 99%
“…Молекулі С 60 притаманна висока відновлювальна здатність; вона може приєднувати до шістьох електронів одночасно. Завдяки цій властивості С 60фуллерени та їхні похідні діють у біологічних системах як ефективні вловлювачі вільних радикалів, зокрема активних форм кисню (ÀÔК), гіперпродукція яких веде до виникнення багатьох патологій [16][17][18], включаючи ішемічні ушкодження м'язів [19,20]. Жодних токсичних ефектів не було зафіксовано за досліджень дії водорозчинних С 60 -фуллеренів у системах in vitro та in vivo [21,22].…”
Section: вступunclassified
“…In our previous studies, it was shown that administration of water-soluble C 60 fullerenes after initiation of ischemic damage leads to significant positive therapeutic effects [ 23 ]. A positive trend has been shown when using them for muscle injury [ 24 ], muscle dysfunction associated with pesticide poisoning [ 25 ], as well as the development of fatigue processes [ 26 ]. All these data stimulated us to test water-soluble C 60 fullerenes as potential therapeutic agents that reduce pathological effects in the muscular system of rats during the development of AT-associated dystrophy.…”
Section: Introductionmentioning
confidence: 99%